Data analytics dalam administrasi pajak di Indonesia: kajian institutional arrangement - Agung Darono (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2020)
This study set out to investigate how institutional arrangements are intertwinned in the implementation of data analytics at the Directorate General of Taxation (DGT) as the Indonesian tax authority. Using an interpretive case study method, this study found a better understanding (verstehen) related to some institutional arrangements which, in this context, worked in three observable forms. These are: (1) the DGT ICT Blueprint has explicitly mentioned that data analytics is a pillar and strategic-application in the development of ICTs; (2) the DGT ICT Governance explicitly provides space for ICT development–i.e. applications or infrastructure, with an end-user computing approach so that ICT user units can fulfill their ICT development needs more flexibly in accordance with guidelines in governance; (3) the interaction of informal practices with various formal provisions needs to be formed so that a formal practice situation related to data analytics is a practice that is in accordance with the organization's ICT governance. This study proposes a conceptual framework that could be used to better understand how institutional arrangements play a key role in the process of implementing data analytics, particularly within a wider range of government organizations